Predation of a mustached bat, Pteronotus sp. (Mormoopidae), by an Amazon tree boa, Corallus hortulanus (Boidae), in the Brazilian Amazon - Barbier, Eder [UNESP]; Pimentel, Narjara Tércia; Bernard, Enrico (FapUNIFESP (SciELO), 2023)
Several bat species use caves as roosts and some of these caves can harbor high concentrations of individuals. Such caves may represent opportunities for certain predators, benefiting from the concentration of potential prey. Here, we report the predation of a Pteronotus bat by a Corallus hortulanus in the Brazilian Amazon. On three occasions over a year, individuals of C. hortulanus were observed around a cave that harbors populations containing tens of thousands of bats. On one occasion, an individual of this snake species was observed preying on a Pteronotus sp. as it left the cave. Our record extends the known diet for C. hortulanus, documenting the predation of a mormoopid bat by this snake species for the first time. This record reinforces the need for longitudinal studies at sites with exceptional bat populations to gain a deeper understanding of the ecological predator-prey relationships involving this diverse group of mammals.
Predação de um morcego bigodudo, Pteronotus sp. (Mormoopidae), por uma suaçuboia, Corallus hortulanus (Boidae), na Amazônia brasileira
Keywords: ambush predator; Carajás National Forest; cave-dwelling bat; Chiroptera; predator-prey interaction